EFFECT OF DIFFERENT STRUCTURAL PARAMETERS ON THE 7075ALUMINUM ALLOY LUG FATIGUE CRACK GROWTH LIFE - ZHOU Song; WANG HongDa; HUI Li; YANG WenJun; DI Jun (Jixie qiangdu)
In order to explore the influence of different structural parameters on the aircraft lug structure crack growth life, using the combination of numerical simulation and test method, fatigue tests were carried out on different structural parameters 7075 aluminum alloy lug samples, the three-dimensional stress intensity factor calculation models of different lugs based on the ABAQUS software was established, the accuracy of the model is verified by comparing the finite element solution with the experimental results and analytical values. Finally, The fatigue crack growth life of lug with different structural parameters was calculated by the Paris formula and fracture mechanics method. The results indicate that under the same stress, with the increase of taper angle, the fatigue crack growth life of the lug structure increases rapidly, and the bottom chamfer have little effect on it.